Lembaga Keuangan Syariah sebagai Mustahiqq Zakah - nafi' mubarok (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2010)
This last decade has witnessed the fast growth of shariah-based financial institutions, which is in form of bank or otherwise. One of many consequences of this growth is ocurrance of bancruptcy. If such condition does happen, islamic legal analysis is conducted over the problem which in turn an Islam financial instiution can be entitled for zakat with the status of debtor. This conclusion is based on three reasonings. The first is the fulfilment of the debt in islamic financial institution for four conditions; (1) the institution is urgently need cash flow, (2) it is for the sake of God’s orders (3) the debt is imminent and (4) the debt is other people’s right. The second is the aspect of ratio legis (‘illah), that giving zakat to that bancrupt instituon is for the reason of (1)uplifting the burden of the debtor (2) raising the dignity of the debtor. The third is recipient aspect, that islamic financial instuitution has fulfilled two things; (1) it is not those who are denied from zakat, (2) sthere is special conditions as a debtor which eligible to accept zakat.